"The influence of listening input and its importance in producing efficient oral communication for students of eleventh grade of business and languages plans at Francisco Morazan High School" - González, Ruth; Sleiman, Jihad; Quintero, Iris; De Lisser, Monica (David, Panamá : UDELAS, 2010)
The following work is about listening input and its impact in those english second language students' oral english communication productions. Taking into consideration the importance that english has around the world being the most worldwide spoken language, and the first language for business and diplomatic relationships.
GENERAL INDEX CHARTS INDEX GRAPHICS INDEX INTRODUCTION CHAPTER I: THE INFLUENCE OF LISTENIGN INPUT AND ITSS IMPORTANCE IN PRODUCING EFFICIENT ORAL COMUNICATION CHAPTER II: THEORITICAL FRAMEWORK 2.1. Input and its importance 2.2. Comprehensible input 2.3. Amount of input 2.4. Rate of input 2.5. Listening input 2.6. Listening input problems 2.7. The inadequate listening input 2.8. Absence of training in listening activities 2.9. Low motivation on students And other more CHAPTER III: METHODOLOGICAL FRAMEWORK CHAPTER IV: ANALYSIS AND INTERPRETATION OF RESULTS CHAPTER V: CONCLUSIONS AND RECOMMENDATIONS Bibliography Annex
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA; ORAL COMMUNICATION -- TESIS DE LICENCIATURA; FACULTAD DE CIENCIAS SOCIALES; ESCUELA DE INGLÉS; LICENCIATURA EN DOCENCIA EN INGLÉS; FRANCISCO MORAZAN HIGH SCHOOL